Metacognitive awareness of reading strategies in students of fourth semester of the University of Quindío (2018)
The aim of this study is to analyze the influence of the metacognitive awareness in reading comprehension strategies of fourth semester students in a languages program. The most relevant concepts in this research are reading comprehension which is defined as one of the sources that highly contribute to the output in ESL. Furthermore, metacognition is most simply defined as thinking about thinking. In addition, the reading strategies are defined as a key tool to have a better reading comprehension. The research was applied to 10 students and a professor of the University of Quindío in the modern languages program which had to make a reading comprehension test and the MARSI test. Besides, 5 of the 10 students were interviewed in order to obtain some specific information. The results showed that the metacognitive awareness enhances students’ performance when using reading strategies. Also, vocabulary is the most common problem when students read. Besides, students of the languages program improved reading through the use of the reading strategies. However, it was demonstrated that the professor has a partial knowledge of metacognition but he promotes critical thinking in students.